Evidence for Carbon Saturation in a Highly Structured and Organic-Matter-Rich Soil - Chung, Haegeun; Ngo, Kathie J; Plante, Alain; Six, Johan (Soil Science Society of America journal, 2010)
Recent studies suggest that mineral soils of temperate ecosystems have a limit in C sequestration capacity, and we reasoned that C saturation will be most evident in soils that are already rich in soil organic C (SOC) and have been exposed to a broad range of C inputs. Therefore, we determined soil C saturation in an agricultural experiment located in Ellerslie, AB, Canada, where organic-matter-rich soils have been cropped to cereal grain for 25 yr. In this experiment, the soils were subject to a broad range of soil C inputs due to a combination of straw retention, tillage, and N fertilization treatments. We determined if C saturation is occurring in soil size fractions that are functionally different. Soils were highly aggregated, with >85% of the soils consisting of macroaggregates. Straw retention, tillage, and N fertilization had no significant effect on the SOC concentration of most soil fractions. Soil organic C concentration of whole soil and soil aggregates isolated from whole soil did not increase with greater soil C inputs. Most of the soil fractions within the large or small macroaggregates did not sequester additional SOC in response to higher soil C inputs. Conversely, SOC concentration in experimental plot soils was significantly lower than that of adjacent grassland soils, which suggests that the maximum C sequestration level for a specific soil type depends on the management practices used. We conclude that C sequestration is governed by C saturation in this highly structured and high-C soil. Our study suggests that soils of temperate ecosystems that are closer to their C saturation capacity may store additional C less effectively than soils that are further away from their saturation capacity.